Non-fatal work related injuries in a cohort of Brazilian steelworkers. Issue 8 (1st August 2000) - Schoemaker, Minouk J; Barreto, Sandhi M; Swerdlow, Anthony J; Higgins, Craig D; Carpenter, Robert G
Abstract : OBJECTIVES: Workers in the steel industry are exposed to various severe hazards. This study investigated risk factors for non-fatal injury occurring in the workplace and during travel to and from work in steelworkers in Brazil. METHODS: Non-fatal work related injuries during employment from January 1977 to September 1992 were analysed in a cohort of 21 732 male workers in the steel plant of USIMINAS, Brazil. RESULTS: There were 14 972 non-fatal injuries during follow up, with 10 891 injuries in the workplace and 4081 during travel to and from work (travel to work injury). The rate of injury in the workplace was 5.6/100 person-years and that of travel to work injury was 2.1/100 person-years. The most common injuries were to hands, arms, and eyes, with 90% of the eye injuries caused by a foreign body. Both rates of workplace and travel to work injury increased significantly with the number of injuries previously experienced, and decreased with number of years in employment and calendar period. The rates of travel to work injury also seemed to decrease with age, but age was not an independent predictor of workplace injury when we controlled for duration of employment. The rate of workplace injury was increased eightfold for workers who had experienced more than six previous injuries compared with those with no previous workplace injuries after adjusting for duration of employment and calendar period. Labourers were most at risk of workplace injury, with about eight injuries per 100 person-years. Travel to work injury was most common among support workers, with nearly half of the travel to work injuries affecting the eyes. CONCLUSION: The rate of injury was high in these steelworks, both for workplace and travel to work injuries. Characteristics of the work areas and the employees can identify high risk groups; protective measures, safety, health training, and injury programmes should concentrate particularly on these groups. Prevention of eye injury needs special attention in steelworks.